Der Decal-Prozess zur Herstellung katalysatorbeschichteter Membranen für PEM-Brennstoffzellen - Frölich, Konstantin (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2015)
This work is a comprehensive analysis of the decal process for production of catalyst coated membranes. Both the process window for the transfer of electrodes from decal foil onto membrane and the effects of the parameters of ink and transfer process on structure and function including process reproducibility shall be investigated. A major component of all those aspects is the selection, implementation and assessment of appropriate characterization methods.